Cryptococcal meningitis epidemiology: 17 years of experience in a State of the Brazilian Pantanal - Joslaine de Oliveira Nunes; Rosianne Assis de Sousa Tsujisaki; Maína de Oliveira Nunes; Gláucia Moreira Espíndola Lima; Anamaria Mello Miranda Paniago; Elenir Rose Jardim Cury Pontes; Marilene Rodrigues Chang (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: This study aimed to describe cryptococcal meningitis (CM) cases and the associated demographic, clinical, and microbiological data obtained from cities in the State of Mato Grosso do Sul in the Midwestern region of Brazil. METHODS: The data from 129 patients with laboratory-confirmed CM admitted from 1997 to 2014 were retrospectively reviewed. The molecular types of Cryptococcus neoformans and Cryptococcus gattii isolated from cerebrospinal fluid were analyzed to determine their geographic distribution. RESULTS: The patients had a mean age of 37 years and consisted mostly of men (76.7%). Most of the Cryptococcus isolates were obtained from patients infected with human immunodeficiency virus (HIV) and included 105 (87.5%) and 5 (55.6%) isolates of C. neoformans and C. gattii complexes, respectively. A restriction fragment length polymorphism (RFLP) analysis of URA5 revealed that most of the isolates were C. neoformans molecular type VNI (89.1%), whereas the molecular types VGII (7%) and VNII (3.9%) were observed less frequently. Notably, 65% of the cases with a time from symptom onset to laboratory diagnosis of more than 60 days resulted in fatalities, and sequelae were observed among the patients who survived. CONCLUSIONS: The present study documents the occurrence of neurocryptococcosis, which is mainly caused by C. neoformans VNI, in Mato Grosso do Sul, Brazil, with probable autochthonous cases in the Brazilian Pantanal, the world’s largest tropical wetland, and a biome where cryptococcosis has not yet been explored.